Analisis Manajemen Pembiayaan Lembaga Keuangan Mikro Syariah Di BMT-UGT Nusantara Capem Kamal - Dwi Utari, Wahyuni; Qadariyah, Lailatul (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2024)
This study examines the management of sharia financing at BMT UGT Nusantara Capem Kamal which faces various problems and challenges. In addition, this study ensures that the BMT UGT Nusantara Capem Kamal institution complies with sharia law in managing its sharia financing. This study applies a descriptive method that is qualitative. This study collects primary data through observation, interviews, and documentation with the Leader of BMT UGT Nusantara Capem Kamal as the key informant. Through literature analysis from various related sources, this study also collects relevant secondary data. From the results of this study, it can be concluded that the management of sharia financing at BMT UGT Nusantara Capem Kamal is in accordance with sharia, effective, efficient, and responsive to the needs and abilities of members and the community, and able to overcome financing risks fairly and wisely. The sharia financial institution BMT UGT Nusantara Capem Kamal, manages sharia financing well, efficiently, and in accordance with sharia. BMT UGT Nusantara Capem Kamal can overcome financing problems and adjust financing products to the needs and abilities of members and the community.